COLLABORATIVE GOVERNANCE IN THE MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUM DESA): CASE STUDY OF THE BUM DESA “SEWU BAROKAH” IN PENATARSEWU VILLAGE - Pramestya, Eka Arum; Wibawani, Sri (DIA: Jurnal Administrasi Publik, 2021)
Development from the village can form a strong village economy that can support the national economy. One of the efforts that can be made in building the village economy is through Village-Owned Enterprises (BUM Desa). The purpose of this research is to describe and analyze the phenomenon of successful management of BUM Desa “Sewu Barokah” in Penatarsewu Village, Tanggulangin District, Sidoarjo Regency in the perspective of collaborative governance. This research is analyzed through the theory of Goldsmith and Kettl which states that there are eight criteria for the success of collaborative governance. This type of research is qualitative descriptive with a case study research design. The technique of determining informants uses the snowball technique, while the data collection techniques are through interviews, observation, a document study, and online data search. Meanwhile, the data validity test was done by triangulating the data source and triangulating the method. This research resulted in findings that the success of BUM Desa “Sewu Barokah” increased its income by three times during the Covid-19 Pandemic because of the involvement of stakeholders. The successful management of BUM Desa “Sewu Barokah” in Penatarsewu Village is by the eight criteria for successful collaborative governance, including networked structure, commitment to a common purpose, trust among the participants, governance, access to authority, distributive accountability/responsibility, information sharing, and access to resources